Fulcrum Rateless Multicast Distributed Coding Design - Rivera, Y.; Gutierrez, I.; Marquez, J. (IEEE access, 2023)
Establishing reliable and efficient multicast services in heterogeneous networks under an erasure channel is one of the current priorities in coding theory, particularly in Network Coding (NC) over data networks. Additionally, the increasing number of clients with mobile devices with high processing capabilities and the prevalence of non-delay tolerant traffic have led to the demand for non-feedback multicast schemes regarding distributed resource management. Current communication platforms lack gradual and dynamic coding control based on the type of data being transmitted. This paper proposes a reliable transmission scheme based on a concatenation of systematic coding and Random Linear Network Coding (RLNC) called Fulcrum coding. This hybrid rateless coding scheme with distributed characteristics allows the implementation of an adaptive resource management system to increase the decoding probability during data reception. The method ultimately results in a higher network throughput and shorter transmission times (RTT) per packet by implementing efficient Forward Error Correction (FEC).